Intestinal Ischaemia-Reperfusion Injury and Semen Characteristics in West African Dwarf Bucks (Nigerian Journal of Physiological Sciences, 2014)
Summary: Increasing production of goats takes their reproductive potential and fertility, into consideration. Gastrointestinal obstructive lesions can set up an intestinal ischaemia-reperfusion. Testicular torsion is an established cause of testicular damage and infertility and is a form of ischaemia-reperfusion injury. This study investigates the effect of intestinal ischaemia-reperfusion (IIR) injury on semen characteristics in WAD bucks. Six healthy adult male WAD goats were divided into two groups of three, a control and IIR group, one hour ischaemia and two hours of reperfusion were achieved in the intestinal ischaemia-reperfusion (IIR) group after all goats underwent a laparotomy. Semen collection was done using the electro-ejaculator method pre-operatively and weekly for four weeks post-operatively. The semen concentration, percentage of normal sperm cells, abnormal sperm cells and percentage abnormality were evaluated. In control animals, there was an increase in semen concentration postoperatively followed by a decrease whereas in IIR animals, a decrease was observed postoperatively till the 4th week. Total normal sperm cells decreased postoperatively and then increased to preoperative levels whereas a decrease was seen in IIR animals till the 3rd postoperative week. Abnormalities in sperm cells, normal head without tail, normal tail without head, bent mid-piece, curved mid-piece and rudimentary tail were all increased by the 4th week in IIR group though the total number of abnormal cells was observed to have decreased. The main effect of intestinal ischaemic-reperfusion injury on the semen characteristics of WAD goats is an increase in abnormalities with an adequate quantity of semen. Many of the abnormalities involved midpiece and tail abnormalities which are very vital to propulsion and may cause an inability of the sperm cells to fertilize. This hitherto silent phenomenon in farm animals may be the reason for iatrogenic causes of infertility.